Nanotechnology: radical new science or plus ça change? - Moriarty, Philip (Collegium Basilea, 2005)
Is a radical nanotechnology involving the construction of macroscopic products via software-directed manipulation of single molecules possible? Are we only a few decades away from a technological utopia where virtually any product may be constructed via molecular manufacturing? These and other similarly provocative questions formed the backdrop for a well-attended debate on nanotechnology held in the University of Nottingham last year (26 August 2005).